Back Cover: Aluminum Acceleration and Reaction Characteristics for Aluminized CL‐20‐Based Mixed Explosives (Prop., Explos., Pyrotech. 6/2018). Issue 6 (14th June 2018) - Liu, Danyang; Chen, Lang; Wang, Chen; Wu, Junying
Abstract : The back cover picture shows a small‐scale confined plate push test which could be used to investigate the effects of aluminum on metal plate acceleration and obtain accurate parameters for the equation of state of the detonation products. The confinement strength of the detonation products was enhanced to twice that of cylinder tests to accelerate the aluminum particle reaction. And the interferometer system was used to continuously measure the plate velocity over time. A series of CL‐20 based aluminized explosives containing various aluminum particle masses and sizes were tested, as well as explosives containing LiF instead of aluminum. By comparing the plate velocity results, the aluminum reaction characteristics could be investigated. The results indicated that the aluminum mainly reacted with CL‐20 detonation products, and the reaction energy was used to accelerate the metal. The reaction rate of 200‐nm aluminum was higher than that of the 2–50‐μm aluminum. Details are discussed in the article by Danyang Liu et al. on page 543 ff.